Rhubarb granule promotes diethylnitrosamine-induced liver tumorigenesis by activating the oxidative branch of pentose phosphate pathway via G6PD in rats. (5th December 2021) - Huang, Hongwu; Liu, Zhenzhen; Qi, Xiaoru; Gao, Nailong; Chang, Jianguo; Yang, Miaomiao; Na, Sha; Liu, Yanyan; Song, Rui; Li, Lu; Chen, Guangliang; Zhou, Hui
Abstract: Ethnopharmacological relevance: Rhubarb is a natural herbal medicine widely used clinically with numerous pharmacological activities including anti-cancer. Specifically, several studies reported that free anthraquinones from Rhubarb suppressed the proliferation of hepatoma cells. Nonetheless, recent studies revealed that Rhubarb caused hepatotoxicity in vivo, confirming its "two-way" effect on the liver. Therefore, the efficacy and safety of Rhubarb in the in vivo treatment of liver cancer should be further elucidated. Aim of the study : This study investigated the presence of hepatoprotection or hepatotoxicity of Rhubarb in diethylnitrosamine (DEN)-induced hepatocarcinogenesis. Material and methods: A total of 112 male Sprague-Dawley rats weighing 190–250 g were enrolled. The rats were induced hepatocarcinogenesis using diethylnitrosamine (0.002 g/rat) until 17 weeks. Starting at week 11, Rhubarb granules (4 g/kg and 8 g/kg) were intragastrically administered daily for 7 weeks. All rats were euthanized at week 20 and the livers were analyzed via non-targeted metabolomics analysis. We established hepatic glucose 6 phosphate (6PG) levels and glucose 6 phosphate dehydrogenase (G6PD) activities to assess the pentose phosphate pathway (PPP). And the liver injuries of rats were analyzed via histological changes, hepatic function, as well as hepatic protein levels of alpha-fetoprotein (AFP), pyruvate kinase isozyme type M2 (PKM2), and proliferating cell nuclear antigen (PCNA). Furthermore, polydatin (0.1 g/kg/d) as a specific inhibitor of G6PD was used to treat rats. Notably, their histological changes, hepatic function, hepatic 6PG levels, hepatic G6PD activities, PCNA levels, and PKM2 levels were recorded. Results: Non-targeted metabolomics revealed that Rhubarb regulated the PPP in the liver of Rhubarb-DEN-treated rats. Besides, Rhubarb activated the oxidative branch of the PPP by activating G6PD (a rate-limiting enzyme in the oxidative PPP) in the liver of Rhubarb-DEN-treated rats. Meanwhile, Rhubarb promoted DEN-induced hepatocarcinogenesis. Moreover, polydatin attenuated the promoting effect of Rhubarb on DEN-induced hepatocarcinogenesis. Conclusions: Rhubarb promoted DEN-induced hepatocarcinogenesis by activating the PPP, indicating that the efficacy and safety of Rhubarb in the treatment of liver cancer deserve to be deliberated. Graphical abstract: Image 1 Highlights: Rhubarb activates the oxidative pentose phosphate pathway in the liver of Rhubarb-DEN-treated rats. Rhubarb promotes DEN-induced hepatocarcinogenesis in rats. Pentose phosphate pathway plays an important role in the synergistic effect of Rhubarb on DEN-induced hepatocarcinogenesis.